A New Similarity between the Critical and Zeno-line Parameters - Apfelbaum, E.M.; Vorob’ev, V.S. (Ukrainian Journal of Physics, 2022)
We set new regularities between the critical and Zeno-line parameters. The most important one has the form Tc/TB + ρc/ρB = S(β), where Tc and ρc are the critical temperature and density. The parameters TB and ρB determine the position of the straight line along which the compressibility factor is equal to 1 on the density-temperature plane. The quantity S(β) is weekly dependent on the critical exponent β: S(β) = 0.64 for the classical value β = 0.5 and 0.67 for β = 1/3. We show that this similarity faithfully describes both the numerical simulation data and experimental data for a wide class of real materials.